Penyuluhan Edukasi Tentang Efektifitas Mc Kenzie Dan William Flexion Exercise Pada Penderita Ichialgia Di Komunitas Lansia Puskesmas Nogosari - Umi Budi Rahayu; Muhammad Raffi; Amelia Dwi Putika Sari; Firnadia Septika Rahajeng; Wahyu Tri Sudaryanto (Jurnal Pengabdian Masyarakat, 2023)
Ischialgia is a condition that often occurs in the elderly and can reduce their quality of life. Therefore, educational outreach regarding Mc Kenzie and William Flexion exercises is important in treating and managing this condition. The results of the study showed that both intervention groups experienced a significant reduction in pain and increased mobility compared to the control group. However, there was no significant difference between the two intervention groups in terms of improving quality of life. These results indicate that both Mc Kenzie and William Flexion exercises are effective in reducing ichialgia pain in the elderly, but there is no significant difference between the two in terms of quality of life.